Agro-smart Caribe: Soil moisture measurement system (2021)
Advances in information and communication technologies provide precision agriculture with more efficient tools for agricultural monitoring systems and the possibility of crop irrigation automation. This paper presents the implementation of a crop field monitoring system based on wireless sensor networks (WSN) with moisture detectors, which are remotely controlled for data collection. The implemented WSN performs information gathering functions from the sensor nodes to the base station. The system is integrated into the internet cloud and together with the hardware and software configuration, adequate energy efficiency is obtained.